Perancangan Game Sederhana Perancangan Game Sederhana Menggunakan Scratch Programming Sebagai Media Pembelajaran Visual Bagi Anak Usia Dini - Yunus Yunus Anis; Artin Bayu Mukti; Sri Mulyani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to design a simple game using Scratch Programming as a visual programming language learning media for early childhood. This article describes the implementation stages of game design and the evaluation of learning media carried out. The literature review reviews the advantages of Scratch Programming as a learning medium for children and previous related research. In the implementation of game design, game concepts are designed using Scratch Programming, and simple game examples are generated. Evaluation of learning media is carried out to collect evaluation data from participants using relevant methods. The results of the evaluation of learning media and the discussion of research findings provide information about the effectiveness of game design using Scratch Programming. The results of this study indicate that designing simple games using Scratch Programming can be an interesting and effective learning medium for young children in learning visual programming languages. The implication of this research is further development in game design and the use of visual programming languages in early childhood education. Suggestions for further research are to involve more participants and explore more complex programming concepts.